Factors Influencing the Decision to Take the Police Entrance Examination Among Crime Prevention Division Students at the Police Training Center, Region 5 - Sriprom, Nichara; Sirisugandha, Thanakorn (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aims to 1. examine the level of opinions regarding motivation, image, attitude, and decision-making in taking the police entrance examination among crime prevention division students at the Police Training Center, Region 5, and 2. study the influence of motivation, image, and attitude on their decision to take the police entrance examination. The sample group consisted of 200 crime prevention division students at the Police Training Center, Region 5. The research instrument was a questionnaire. Descriptive statistics, including percentage, mean, and standard deviation, were used for data analysis. Inferential statistics were applied using multiple regression analysis with the Enter method. Research results found that 1. the level of opinions regarding motivation had the highest influence on the decision to take the police entrance examination among crime prevention division students at the Police Training Center, Region 5, followed by attitude, which was at a high level, and image, which was also at a high level, respectively 2. the results of multiple regression analysis using the Enter method indicated that motivation, image, and attitude significantly influenced the decision to take the police entrance examination at a statistical significance level of 0.05